2017
DOI: 10.1161/jaha.117.007402
|View full text |Cite
|
Sign up to set email alerts
|

Residual Risk of Atherosclerotic Cardiovascular Events in Relation to Reductions in Very‐Low‐Density Lipoproteins

Abstract: BackgroundIt is uncertain whether pharmacological reductions in very‐low‐density lipoproteins (VLDLs), and their component triglyceride and cholesterol could reduce residual risk of atherosclerotic cardiovascular disease (ASCVD) events among individuals in whom low‐density lipoprotein cholesterol (LDL‐C) has been adequately lowered. We examined whether individuals with greater on‐statin reductions in VLDL‐related measures—beyond reductions in LDL‐C—were at further reduced risk of ASCVD.Methods and ResultsIn 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 32 publications
(60 reference statements)
2
46
0
2
Order By: Relevance
“…Experimental models and human genetics have indicated that triglyceride-rich lipoproteins (TRL) play a causal role in the pathogenesis of CVD 2 . Post-hoc analyses of statin trials have further shown that reductions of TRL is associated with lower cardiovascular event risk independently of the LDL cholesterol reduction achieved from statins 3,4 . These observations have accelerated the development of novel TRL-lowering therapeutics for CVD prevention, with drug targets informed by recent discoveries from genetic studies 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental models and human genetics have indicated that triglyceride-rich lipoproteins (TRL) play a causal role in the pathogenesis of CVD 2 . Post-hoc analyses of statin trials have further shown that reductions of TRL is associated with lower cardiovascular event risk independently of the LDL cholesterol reduction achieved from statins 3,4 . These observations have accelerated the development of novel TRL-lowering therapeutics for CVD prevention, with drug targets informed by recent discoveries from genetic studies 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The causal consequences of these differences in mediumsized and large VLDL particles, that are rich in triglycerides, remains unclear and warrants further investigations; whereas IDL and the smallest VLDL particles can penetrate the arterial wall to cause atherosclerosis, it is commonly perceived not be to the case for larger VLDL particles (37,46). We also observed a difference in lowering of VLDL-cholesterol levels; the cholesterol concentrations of VLDL particles are strongly associated with risk of myocardial infarction (43) and some studies have suggested that VLDL-cholesterol could underpin the link between triglycerides and cardiovascular risk (37,40). If these VLDL particles do play a causal role in vascular disease, the discrepancy between statin therapy and PCSK9 inhibition could translate into slightly more potent cardiovascular risk reduction for the same LDL-C lowering for statins as compared with PCSK9 inhibition.…”
Section: Discussionmentioning
confidence: 68%
“…This could potentially contribute to subtle differences in potency for cardiovascular event lowering for the same LDL-C lowering (6), since recent evidence suggests that VLDL-cholesterol and other triglyceride-rich lipoprotein measures may causally contribute to the development of coronary heart disease independent of LDL-C (37-39). Moreover, trial data show that VLDL-cholesterol is a stronger predictor of cardiovascular event risk than is LDL-C among patients on statin therapy (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In T2DM, possible candidates for residual risks include sdLDL [12], postprandial hypertriglyceridemia [25], and TG-rich lipoproteins [21,25,26]. Our findings may provide a unique approach to this important "beyond statin" issue [21][22][23][24]. Previous studies have reported the effects of anagliptin on the lipid profiles of patients with type-2 diabetes, but these were not controlled for statin treatment [14,19,27].…”
Section: Discussionmentioning
confidence: 83%
“…Although statins are beneficial in preventing ASCVD [3,4], residual risk after statin treatment should be considered in specific conditions [5,6,12,[21][22][23][24][25][26]. In T2DM, possible candidates for residual risks include sdLDL [12], postprandial hypertriglyceridemia [25], and TG-rich lipoproteins [21,25,26].…”
Section: Discussionmentioning
confidence: 99%